Perceptions and Portrayals of Skin Cancer among Cultural Subgroups. - Kelly, Stephanie; Miller, Laura E; Ahn, Ho-Young; Haley, J Eric (ISRN dermatology, 2014)
Health communication scholars have a responsibility to be certain that both healthcare practitioners and government agencies accurately communicate health information to the public. In order to carry out this duty, health communication scholars must assess how messages are being received and if they are being received at all by the public. This paper details a two part study which assesses this phenomenon within the context of skin cancer. Study 1 utilized 29 in depth qualitative interviews to identify subcultures among college students whose communication puts them at risk for skin cancer by encouraging poor sun exposure behaviors. The results indicate that farmers, African Americans, and individuals who regularly participate in outdoor athletics are at risk groups. Study 2 reports a content analysis of the known population of skin cancer Public Service Announcements (PSAs) available via the internet in 2013. The aforementioned groups were not present in any of the PSAs. Detailed results and implications are discussed.
Keywords: dept.com

Consumers' optimism bias and responses to risk disclosures in direct-to-consumer (DTC) prescription drug advertising: the moderating role of subjective health literacy - Ahn, Ho-Young (Anthony); Park, Jin Seong; Haley, Eric (Journal of Consumer Affairs, 2014)
Despite a substantial body of research in direct-to-consumer advertising (DTCA) for prescription drugs, what is missing from the existing discussion on the risk disclosure in DTCA is a focus on the roles of individual motivation and ability to process risk information. Guided by the Elaboration Likelihood Model (ELM) and the Motivation-Ability-Opportunity framework, the current study examines the roles of the consumer's optimism bias and subjective health literacy in responding to the risk disclosure in DTCA. By analyzing survey data (N = 404), the study reveals that: (1) consumers who show a tendency to believe that they are at less risk of experiencing adverse reactions to prescription drugs than their peers are less likely to pay attention to the risk disclosure or intend to seek further information about the health risks of drugs, (2) the relationship between optimism bias and information-seeking intentions is stronger for consumers with high subjective health literacy than for those with low health literacy. Implications and recommendations are provided.
Keywords: dept.com